2022
DOI: 10.1002/anie.202216592
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Dissolved Isostructural Polyoxovanadates to Construct Single‐Atom‐Site Catalysts for Efficient CO2Photoreduction

Abstract: We explored a co-dissolved strategy to embed mono-dispersed Pt center into V 2 O 5 support via dissolving [PtV 9 O 28 ] 7À into [V 10 O 28 ] 6À aqueous solution. The uniform dispersion of [PtV 9 O 28 ] 7À in [V 10 O 28 ] 6À solution allows [PtV 9 O 28 ] 7À to be surrounded by [V 10 O 28 ] 6À clusters via a freeze-drying process. The V centers in both [PtV 9 O 28 ] 7À and [V 10 O 28 ] 6À were converted into V 2 O 5 via a calcination process to stabilize Pt center. These double separations can effectively preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Polyoxometalates (POMs) are a class of functional materials assembled with polymetallic and oxide clusters, which have received considerable attention due to their versatile structures and wide applications in catalysis, coordination chemistry, materials science, biological medicine, and photochemistry. Especially for catalysis, these materials have strong Brønsted acidity and could be used as both acid catalysts and efficient oxidation catalysts for rapid and reversible multisite oxidation–reduction transformation. , However, the features of good solubility and easily transferred structural patterns limited the application of these materials in heterogeneous catalysis. As a unique class of porous crystalline materials, metal–organic frameworks (MOFs) constructed from metal ions/clusters and well-designed organic ligands have displayed great potential due to their tunable framework patterns and stable porosity with high surface areas. Taking these into account, POM-based metal–organic frameworks (POMOFs) could combine both the advantages of POMs and MOFs within one single system, which greatly enhances the stability of POM units to exploit their catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyoxometalates (POMs) are a class of functional materials assembled with polymetallic and oxide clusters, which have received considerable attention due to their versatile structures and wide applications in catalysis, coordination chemistry, materials science, biological medicine, and photochemistry. Especially for catalysis, these materials have strong Brønsted acidity and could be used as both acid catalysts and efficient oxidation catalysts for rapid and reversible multisite oxidation–reduction transformation. , However, the features of good solubility and easily transferred structural patterns limited the application of these materials in heterogeneous catalysis. As a unique class of porous crystalline materials, metal–organic frameworks (MOFs) constructed from metal ions/clusters and well-designed organic ligands have displayed great potential due to their tunable framework patterns and stable porosity with high surface areas. Taking these into account, POM-based metal–organic frameworks (POMOFs) could combine both the advantages of POMs and MOFs within one single system, which greatly enhances the stability of POM units to exploit their catalytic properties.…”
Section: Introductionmentioning
confidence: 99%
“…12−18 Especially for catalysis, these materials have strong Brønsted acidity and could be used as both acid catalysts and efficient oxidation catalysts for rapid and reversible multisite oxidation−reduction transformation. 19,20 However, the features of good solubility and easily transferred structural patterns limited the application of these materials in heterogeneous catalysis. As a unique class of porous crystalline materials, metal−organic frameworks (MOFs) constructed from metal ions/clusters and well-designed organic ligands have displayed great potential due to their tunable framework patterns and stable porosity with high surface areas.…”
Section: Introductionmentioning
confidence: 99%
“…POMs have been widely used as catalysts [18][19][20] for organic oxidations due to their rich redox chemistry. 21 Meanwhile, a new separation technique has been developed by controlling the pore structure in a POM cluster. 22 It has been reported that many transition metal-incorporating polyoxometalates (POMs) exhibit reversible redox behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are a class of excellent photocatalysts because they can act as electronic sponges in storing or releasing electrons through redox reactions, which are favorable for efficient electron transfer through type I reactions and generating the single ROS • O 2 − . [30][31][32][33] In particular, the Dawson-type polyanion [P 2 W 18 O 62 ] 6− can accept up to 18 protons and electrons in water, displaying outstanding proton-coupled electron redox activity. 34,35 It is an exciting challenge to introduce the active center of binuclear metal monooxygenase, photosensitizer TPT and electronic sponge POM to construct a POMOF-based artificial monooxygenase model by utilizing the crystal engineering strategy (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Polyoxometalates (POMs) are a class of excellent photocatalysts because they can act as electronic sponges in storing or releasing electrons through redox reactions, which are favorable for efficient electron transfer through type I reactions and generating the single ROS ˙O 2 − . 30–33 In particular, the Dawson-type polyanion [P 2 W 18 O 62 ] 6− can accept up to 18 protons and electrons in water, displaying outstanding proton-coupled electron redox activity. 34,35…”
Section: Introductionmentioning
confidence: 99%